Pertimbangan Etika dan Agama Dalam Aplikasi Ilmu - Madina, Siti; Asri, Syamsul (Yayasan Daarul Huda Kruengmane, 2024)
Ethics in Islam cannot be separated from the science of morals in various branches of Islamic religious knowledge. Therefore, ethics in Islam (it could be said) is identical to the science of morals, namely the science of virtues and how to obtain them so that humans will be adorned with them and the science of despicable things and how to avoid them so that humans are free from them. Ethics, on the other hand, is often considered the same as morals. Science and religion are human achievements, which in essence, arise from the same spirit so that humans can survive. In other words, science and religion were born out of necessity, namely to answer various kinds of challenges that humans always face in their existence.